Roles of Inflammation in Neurodegenerative Diseases - Singsai, Kanathip; Sattayasai, Jintana (Journal of Basic and Applied Pharmacology, 2017)
Inflammation is a biological response to injury. Although inflammatory processes have many benefits and are related to tissue repairing processes, out of control of the inflammatory response might facilitate the production of neurotoxic factors and cause many chronic diseases including neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s diseases, amyotrophic lateral sclerosis, and multiple sclerosis. Actually, neurodegenerative diseases are induced by specific-disease mechanisms, with different sites of injury and specific pathophysiologic responses to inflammatory processes. Interestingly, these diseases have been involved with inflammatory processes. Triggering process with inducers, sensors, transducers, and effectors can induce the amplification of inflammatory responses leading to neurotoxicity and neuronal death. Therefore, inhibition of the inflammatory responses might reduce the progression of the diseases. Reviewing the role of anti-inflammatory agents in nervous system might be benefit for preventing or treating neurodegenerative diseases.